Improving surface quality in selective laser melting based tool making - Filippo Simoni; Andrea Huxol; Franz-Josef Villmer (Journal of Intelligent Manufacturing, 2021)
In the last years, Additive Manufacturing, thanks to its capability of continuous improvements in performance and cost-efficiency, was able to partly replace and redefine well-established manufacturing processes. This research is based on the idea to achieve great cost and operational benefits especially in the field of tool making for injection molding by combining traditional and additive manufacturing in one process chain. Special attention is given to the surface quality in terms of surface roughness and its optimization directly in the Selective Laser Melting process. This article presents the possibility for a remelting process of the SLM parts as a way to optimize the surfaces of the produced parts. The influence of laser remelting on the surface roughness of the parts is analyzed while varying machine parameters like laser power and scan settings. Laser remelting with optimized parameter settings considerably improves the surface quality of SLM parts and is a great starting point for further post-processing techniques, which require a low initial value of surface roughness.
Keywords: 620; Direct rapid tooling; Toolmaking; Additive manufacturing process chain; Process control; Production systems; Selective laser melting; Surface roughness; Laser surface remelting